LES RESPONSABLES PÉRUVIENS DANS LA CAMPAGNE MARITIME DANS LE PACIFIQUE (AVRIL-OCTOBRE DU 1879) (Tzintzun, Revista de Estudios Históricos, 2022)
The correspondents of the Peruvian newspapers that covered the alternatives ofthe naval campaign of the War of the Pacific (April-October 1879) contributedto satisfy the information needs of public opinion. In addition, they allowed thecreation of representations and imaginaries linked to the archetypes of behaviorand patriotic virtues of the Peruvians, as well as the construction of the Chileanotherness. These writings collaborated in delineating the contemporary and futureinterpretative canon of the conflict.
Keywords: press; War of the Pacific; correspondents; Peru